(3GKHGJ eG dGHO efg oHO deQjO Gdhbha Ydi MbjbI GdOjfGQ hGdOQge hGdUGY hGdoeOs - (3CHh GdYHGS CMeO Hf eMeO Hf CMeO GddNei GdYRai GdSHJis
(3ChdgG (B:s
(3jHOC Hbhdg (B: (3hGdhRf Cf eGdReg GSe deNJhe hGdbajR hGdhchc hGdeO hGdUGY agh cjd s
(3BNQgG (B:s
(3jfJgi CKfGA GdcdGe Ydi (B( (3GdhbjI (B) (3Hbhdg (B: (3bGd Gdabjg CHh GdYHGS QVi Gddg Yfg hChbjI bjfG ai GdCegGJ s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP eMeO Gdefhfi HGdQHGW ef GdecJHGJ GdNGUI (B(164) s
Keywords: (3Gdabg GdeGdcjs